SPATIAL AND ECONOMIC ANALYSIS OF POTENTIAL AGRICULTURAL LAND AND ITS INFLUENCE ON THE RUPIAH EXCHANGE RATE AGAINST USD: A LITERATURE REVIEW - Nikma Fista Safrina; Raden Aswin Rahadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The food crisis has become a global issue for countries. According to Law No.18/2012, rice is an important commodity that must be maintained to ensure food availability for consumption fulfilment. Rice trade performance analysis, Indonesia’s Import Dependency Ratio remained within acceptable limits but increased significantly beyond the 2% threshold, reaching 8.14 by 2023. Regarding Indonesia’s economic goals of being a developed country, Mr. Prabowo initiated the Astacita program, the presidential mission aiming to strengthen national security and promote self-reliance in food, energy, water, creative, green, and blue economies. The potential of successful national or world food estate is the stability of rupiah depreciation against USD. The Indonesian government’s initial food estate was started a long time ago. The last program is the Food Estate Program, which expands agricultural land and enhances productivity. However, past projects—such as the Central Kalimantan Food Estate—struggled with suitability issues. Under President Prabowo’s astacita Initiative, the administration has targeted developing 1 million hectares of new rice fields annually from 2025 to 2029, to reduce import dependence and strengthen national food security. This study finds that spatial analysis and economic modelling could assess agricultural land suitability for rice cultivation and its potential impact on the trade balance. Through a structured literature review, this research integrates insights from historical trade performance, economic elasticity models, and geospatial methodologies to identify recommendations for food estate locations. The findings link exchange rates and export performance, showing a relation between depreciating Rupiah, which can improve rice export competitiveness while raising concerns about trade imbalances and rising costs for agricultural inputs. If the national food estate program is successful, how much will the specific region produce a commodity for export, and how it will affect the Rupiah appreciation should be further explored. Future research should further explore trade elasticity dynamics, regional agricultural comparisons, and the broader economic implications of food estate expansion to refine national agricultural and financial policies.